Cross-Cultural Narrative Structures in Aḥbabtuka Aktsar Mimma Yanbaghī and Antara Oxford dan Munjid: A Comparative Narratological Analysis - Deskananda Deskananda; Zulkhairi Zulkhairi; Aulia Ivan; Berdan Aiyub; Shaliha Chairunnisa Ahsana Amalan (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study aims to describe and explain the comparison of novel structures contained in two different novels: Aḥbabtuka Aktsar Mimma Yanbaghī by Atheer ‘Abdullah An-Nasyamī and Antara Oxford dan Munjid by Deskananda. The method used in this research is a qualitative descriptive method. The primary data consist of the novels Aḥbabtuka Aktsar Mimma Yanbaghī and Antara Oxford dan Munjid, while secondary data and other relevant information are collected from books, journals, scholarly works, and websites that discuss the research problems of both works. Data collection techniques include close reading, note-taking, and document analysis using structuralism theory and a comparative literary approach. The results show several similarities and differences in the narrative structure of both novels. The similarities include: the main theme of the novel, the use of flashback narrative technique, similar epilogues, character development of the protagonists, general settings of time and place, and the use of the first-person point of view. The differences lie in: the supporting themes, the schematic structure of the plot, the selection of main and supporting characters, the specific settings of time and place, and the author's narrative perspective.